A Visual Identity Design of Trio Jaya Bidaran & Ciput Cake in Blitar City - Ayun, Qurrota; Costa Rica El Chidtian, Aileena Solicitor; Wulandari, Sri (Universitas Ciputra, 2024)
The UMKM that we chose is the business of making Bidaran and Ciput cakes